Recovery from Talaromyces marneffei involving the kidney in a renal transplant recipient: A case report and literature review. Issue 4 (7th June 2017) - Peng, Juan; Chen, Zhiyong; Cai, Ruiming; Huang, Xianen; Lin, Liying; Liang, Weixiang; Xiong, Zhongtang; Chen, Juan; Chen, Hui; Yang, Yuexin; Liu, Shaoyan; Jiang, Qingping
Abstract: Talaromyces marneffei is an emerging opportunistic infection among immunocompromised patients. We observe the first native case of disseminated T. marneffei involving the kidney in a renal transplant recipient in mainland China. We describe the comprehensive clinical course, and ultrasound imaging of renal transplant biopsy, pathologic images, and electron microscopy observation of the biopsy specimen, highlighting the relevance of biopsy findings and the blood culture. We also focus on the treatment and good outcome of the patient. Then we review the literature and show the additional 10 reported cases of T. marneffei in renal transplant recipients. In addition, we discuss the new methods of rapid diagnosis of T. marneffei . In brief, timely diagnosis and proper treatment of T. marneffei infection is important in renal transplant recipients.